From Territoriality to Borderscapes: The Conceptualisation of Space in Border Studies. Issue 2 (15th March 2023) - Peña, Sergio
ABSTRACT: The objective of this article is to analyse the conceptualisation of space in border studies. My interest in the subject arises because recent articles published on diverse outlets of border studies have advanced the notion that borders are on the move and not necessarily located where it is expected—at the line shared by two sovereign nations. Instead, scholars argued that borders have become dislocated, displaced and can be found in-between, anywhere even if they have been out-sourced or placed off-shore. This notion of borders "everywhere" gives the sensation that borders are becoming a-spatial, a-territorial, space no longer matters, and geography is dead. This paper challenges that view. Thus, the main contribution this paper makes is to bring back space into border theory by tracing and reinserting spatial concepts into the discussion of border studies. The central argument in the paper is that space and borders are closely intertwined—like the ying and yang; borders are space. I argue that we can advance the theorisation of borders from a spatial perspective by delving deeper into concrete spatialisations such as micro spaces or heterotopias (besides the camp. Prison, mental hospitals, etc.) where bordering practices take place.